Implementation of Moora's Multi Criteria Decision Making (MCDM) Method in Determining SMEs Indicators After the Covid-19 Pandemic - Yunitarini, Rika (International Conference on Sciences Development and Technology, 2022)
After the covid pandemic for almost 2 years, it has paralyzed the small and medium enterprise (SMEs) sector. Several government policies during the pandemic resulted in several SMEs experiencing bankruptcy and decline, especially with regard to production, marketing, and labor. After almost 2 years, SMEs began to slowly rise to organize its existence. This research is used to identify indicators that influence to SMEs after the COVID-19 pandemic. The problem of this research is there are many SMEs in Bangkalan Madura, many SMEs do not know about online marketing, marketplace, and lack of technological knowledge to accelerate production and marketing. The Moora method is used to determine the indicators that have the most influence on the sustainability of SMEs in the face of the Covid-19 pandemic.